2019
DOI: 10.1128/iai.00732-19
|View full text |Cite
|
Sign up to set email alerts
|

Taurine Alleviates Schistosoma-Induced Liver Injury by Inhibiting the TXNIP/NLRP3 Inflammasome Signal Pathway and Pyroptosis

Abstract: Schistosomiasis is a parasitic helminth disease that can cause severe inflammatory pathology, leading to organ damage, in humans. During a schistosomal infection, the eggs are trapped in the host liver, and products derived from eggs induce a polarized Th2 cell response, resulting in granuloma formation and eventually fibrosis. Previous studies indicated that the nucleotide-binding oligomerization domain-, leucine-rich repeat-, and pyrin domain-containing protein 3 (NLRP3) inflammasome is involved in schistoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 46 publications
2
33
0
Order By: Relevance
“…Inflammation plays an important role in the development and progression of liver fibrosis [36,37]. Previously, S. mansoni infection has been shown to activates NLRP3 inflammasomes in vitro and in vivo models [4][5][6]. Since Sch B has been shown to ameliorates inflammasome activation in various inflammatory models [27][28][29]33], to also verify the protective effects of Sch B against S. mansoni-induced liver fibrosis, we examined the effects of Sch B on the NLRP3 inflammasome pathway.…”
Section: Schisandrin B Reduces S Mansoni-induced Inflammation Through Inhibition Of Inflammasomementioning
confidence: 99%
See 1 more Smart Citation
“…Inflammation plays an important role in the development and progression of liver fibrosis [36,37]. Previously, S. mansoni infection has been shown to activates NLRP3 inflammasomes in vitro and in vivo models [4][5][6]. Since Sch B has been shown to ameliorates inflammasome activation in various inflammatory models [27][28][29]33], to also verify the protective effects of Sch B against S. mansoni-induced liver fibrosis, we examined the effects of Sch B on the NLRP3 inflammasome pathway.…”
Section: Schisandrin B Reduces S Mansoni-induced Inflammation Through Inhibition Of Inflammasomementioning
confidence: 99%
“…Inflammasomes have been found to regulate important aspects of tissue inflammation. The activation of NOD-like receptor family pyrin domain-containing three (NLRP3) inflammasomes has been shown during Schistosoma-infected liver fibrosis [4][5][6]. Once NLRP3 is activated, it recruits an adaptor protein, apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC), and induces activation of caspase-1.…”
Section: Introductionmentioning
confidence: 99%
“…During human NAFLD/NASH, GSDMD and its N-terminal peptide (GSDMD-N) are upregulated, besides MCD-fed Gsdmd −/− mice showed decreased severity of steatosis and inflammation comparing to WT (52). During Schistosoma infection, Liu and colleagues (2019) demonstrated that S. japonicum induces expression of the GSDMD-N in the liver, and that this expression is modulated by NLRP3 sensor (53). In addition, it has been reported that SEA from S. japonicum eggs induces pyroptosis in HSCs (54).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidences show that in ammatory processes are crucial for the pathogenesis and progression of serious liver diseases [10,13,15] . NLRP3 in ammasome has signi cant role in the innate immune system involving the in ammatory response [17,24] . Here, we nd that the expression of NLRP3, Caspase-1, and IL-1β in the in ammatory marginal zone of HAE patients are signi cantly increased.…”
Section: Discussionmentioning
confidence: 99%
“…The NLRP3 in ammasome is an important participant in in ammatory responses and has been closely associated with in ammation in various liver diseases, including liver cancer (Wei 2014, Saber 2010, Wei 2019) [10][11][12] , viral hepatitis (Ding 2019, McRae 2016) [13,14] , non-alcoholic fatty liver (Sun 2020, Dwivedi 2020) [15,16], and schistosomiasis (Liu 2019, Chen 2019) [17,18] . However, the role and clinical signi cance of the NLRP3 in ammasome in HAE remain unclear.…”
Section: Introductionmentioning
confidence: 99%